Efficacy of topical photodynamic therapy in the treatment of erythroplasia of Queyrat (Dermatology Reports, 2020)
Erythroplasia of Queyrat (EQ) is an intraepidermal carcinoma in situ presenting clinically as a sharply demarcated, slightly raised erythematosus plaque on the glans penis or the inner side of the foreskin. Various treatment modalities for EQ have been proposed, including electrocautery and curettage, topical 5-floururacil cream, imiquimod cream, isotretinoin, cryotherapy, laser therapy, radiotherapy, ingenol mebutate gel and photodynamic therapy (PDT). Most of these treatments are limited by low clearance rates and frequent relapses. Surgical treatment including local excision, Mohs micrographic surgery and partial or total penectomy, ensures adequate healing rates. However, discomfort consequent to surgical treatment might be unacceptable. Topical PDT using the methyl ester of 5-aminolaevulinic acid (MAL) is an established non-surgical treatment of cutaneous precancerous lesions and skin cancers. We present the case of a 60-year-old uncircumcised man affected by EQ of the penis successfully treated with MAL-PDT, performed five times, two weeks apart, with no recurrences after 6 years.